Comparison of cellular responses of cultured fibroblasts from Iriomote wild cats and domestic cats exposure to polyinosinic:polycytidylic acid - Masafumi Katayama; Ayusa Kataoka; Tomokazu Fukuda; Manabu Onuma (PLoS ONE, 2025)
The Iriomote wild cat is endemic to Iriomote Island. The total population is only 100 cats. These cats are thus listed as critically endangered on the IUCN Red List. Infectious disease is a risk factor for further reducing the Iriomote wild cat population. RIG-I, MDA5 and TLR3 are important sensors that recognize host viral defense responses. IL6, Mx, and OAS are downstream genes of RIG-I and MDA5. Polyinosinic:polycytidylic acid (poly(I:C)) stimulates the RIG-I, MDA5 and TLR3 in many animals. In this study, we thus tried to compare RIG-I, MDA5, and TLR3 responses after exposure to the poly(I:C) in domestic cat- and Iriomote wild-cat-derived fibroblasts. This study also compared the expression of downstream gene (IL6, Mx, and OAS) of RIG-I and MDA5. This study analyzed the genes expressions of domestic cat- and Iriomote wild-cat-derived fibroblasts after exposure the poly(I:C), using real-time PCR and RNA-seq. In addition to these genes expression, this study compared the gene sequence of RIG-I and MDA5 between domestic cat and Iriomote wild cat with information of public database. RIG-I and MDA5 levels were increased in both domestic cat- and Iriomote cat-derived fibroblasts after poly(I:C) exposure, while TLR3 expression did not change dramatically after poly(I:C) exposure. A comprehensive gene expression analysis revealed that molecular responses of fibroblasts derived from domestic cats and those derived from Iriomote wild cats to poly(I:C) exposure were similar. Furthermore, RIG-I and MDA5 sequences are similar between domestic and Iriomote wild cat. Our results suggested that poly(I:C) mainly stimulates RIG-I and MDA5 among the three genes (RIG-I, MDA5 and TLR3) examined in this study, and the RIG-I and MDA5 mediated molecular responses to poly(I:C) exposure are similar in domestic and Iriomote wild cats fibroblasts. To the best of our knowledge, this is the first study to compare the RIG-I and MDA5 responses of Iriomote wild cats and domestic cats after poly(I:C) exposure. This study provides valuable insights into the cellular response mediated by RIG-I and MDA5 in the Iriomote wild cat.